2017
DOI: 10.1144/sp461.3
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characteristics of the ice cores obtained after the first unsealing of subglacial Lake Vostok

Abstract: Drilling fluid (DF) is one of the main sources of chemical and biological contamination of deep ice cores and lake water samples in the exploration of Subgalcial Antarctic Lake Environments (SALE). In this study, we investigated the contamination of an ice core that represented the first samples of refrozen lake water obtained 1 year after the unsealing of Lake Vostok in 2012. We show that these samples contain inclusions of the DF with a concentration of at least 16.7 mg l−1 (0.0019% or 19 ppmv). This makes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Reports have shown that mechanical drilling using hydrocarbon-based drilling fluids can contaminate ice core and subglacial water samples as well as the subglacial environment itself (Christner and others, 2005; Alekhina and others, 2007, 2018; Talalay and others, 2014). For this reason, the first clean access to a subglacial lake (Whillans Subglacial Lake, SLW) by the Whillans Ice Stream Subglacial Access Research Drilling (WISSARD) project during the 2012–13 austral summer, used a hot water drill fitted with clean access technology (Priscu and others, 2013; Christner and others, 2014; Tulaczyk and others, 2014; Rack, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that mechanical drilling using hydrocarbon-based drilling fluids can contaminate ice core and subglacial water samples as well as the subglacial environment itself (Christner and others, 2005; Alekhina and others, 2007, 2018; Talalay and others, 2014). For this reason, the first clean access to a subglacial lake (Whillans Subglacial Lake, SLW) by the Whillans Ice Stream Subglacial Access Research Drilling (WISSARD) project during the 2012–13 austral summer, used a hot water drill fitted with clean access technology (Priscu and others, 2013; Christner and others, 2014; Tulaczyk and others, 2014; Rack, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The first accessing of an Antarctic subglacial lake took place in February 2012 at Lake Vostok in central East Antarctica (Lukin and Vasiliev, 2014; Lipenkov and others, 2016). Refrozen lake water samples were later recovered using an ice core drill, although contamination from the hydrocarbon-based drilling fluids remains an issue (Alekhina and others, 2018). For this reason, other lake access drilling has used hot water drills fitted with clean access technology (Rack and others, 2014; Rack, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Drilling fluid is required to prevent lithostatic pressure from causing plastic collapse of the borehole, to lubricate the drill head and to remove ice chips from the borehole (Talalay & Gundestrup 2002). Controlling microbial contamination of hydrocarbon-based drilling fluids is difficult (Christner et al 2005, Bulat 2016, Alekhina et al 2018). Hydrocarbon-based drilling fluids are also not ideal for accessing subglacial habitats due to concerns of chemical contamination (Talalay & Gundestrup 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrocarbon-based drilling fluids are also not ideal for accessing subglacial habitats due to concerns of chemical contamination (Talalay & Gundestrup 2002). For example, mechanical drilling using a kerosene-based fluid densified with CFCs was used to access Vostok Subglacial Lake, but the frozen lake water recovered by coring was heavily contaminated with the kerosene-based and CFC-laden drilling fluid, which compromised scientific interpretation (Alekhina et al 2018). Hot-water drilling was used to access Whillans Subglacial Lake (SLW; West Antarctica) (Tulaczyk et al 2014), a subglacial lake in the Grímsvötn caldera (Iceland) (Gaidos et al 2004), the bed of Kamb Ice Stream (West Antarctica) (Engelhardt et al 2000), a sub-ice shelf marine cavity (West Antarctica) (Vick-Majors et al 2015) and a surge-type valley glacier (Alaska) (Truffer et al 1999).…”
Section: Introductionmentioning
confidence: 99%